2021
DOI: 10.9734/aprj/2021/v7i230153
|View full text |Cite
|
Sign up to set email alerts
|

Response of Growth, Yield and Essential Oil of Geranium Plants to Surface Irrigation and Humic Acid Treatments

Abstract: Water is among the most important factors affected growth, yield and quality of medicinal and aromatic plants since its deficiency may cause serious growth harms and yield losses. Egypt suffers from a scarcity of water, so each drop should be preserved. Therefore, the objective of the present study was to determine the suitable irrigation treatment (120, 100 and 80% ETo (evapotranspiration) and humic acid amounts (control), 1.0, 1.5 and 2.0 cm/L) that attain the highest growth, yield and essential oil of geran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…HA application improved hormonal and ROS balance [46]; as well as activation of antioxidant enzymes and accelerating organic solute accumulation [47], which was ultimately reflected in plant growth [22]. Moreover, the encouraging role of HA can be linked to its impact on boosting interior carbon dioxide concentration and leaf thickness, improving cell water maintenance and boosting water use efficiency [30]. Additionally, HAs' positive effect could be due to the hormone-like activity or may be connected to encouraging indole acetic acid assimilation, which accelerates cell division and enlargement as well as eradicating ROS [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA application improved hormonal and ROS balance [46]; as well as activation of antioxidant enzymes and accelerating organic solute accumulation [47], which was ultimately reflected in plant growth [22]. Moreover, the encouraging role of HA can be linked to its impact on boosting interior carbon dioxide concentration and leaf thickness, improving cell water maintenance and boosting water use efficiency [30]. Additionally, HAs' positive effect could be due to the hormone-like activity or may be connected to encouraging indole acetic acid assimilation, which accelerates cell division and enlargement as well as eradicating ROS [48].…”
Section: Discussionmentioning
confidence: 99%
“…Nofal et al [29] found that the spraying of HA significantly increased Erantheumum pilchellum plant height, leaf number per plant, fresh and dry weight, flower diameter and chlorophyll content. Hammam et al [30] revealed that spraying geranium plants with HA significantly increased plant height, shoot fresh and dry weight, proline concentration and water use efficiency. Previous research has suggested that the beneficial effects of HA can be attributed to the activation of several metabolic enzymes, improving plant water status, maintaining ion and redox homeostasis and promoting secondary metabolite assimilation [31].…”
Section: Introductionmentioning
confidence: 99%